Perceptions of Trust: Communicating Climate Change to Cattle Producers - Ricky W Telg; Lisa Lundy; Cassie Wandersee; Saqib Mukhtar; David Smith; Phillip Stokes (Journal of Applied Communications, 2018)
The Cattle and Climate Conversations Workshop for Cooperative Extension and Natural Resources Conservation Service, the last activity funded through a multi-regional United States Department of Agriculture’s National Institute of Food and Agriculture (USDA NIFA) grant, took place in October 2016 in Denver, Colorado, for Extension and Natural Resources Conservation Service (NRCS) representatives in the Southwest and Mountain West who work extensively with cattle producers. The purpose of this study was to identify how Extension agents and NRCS personnel in this workshop viewed the issue of “trust,” as it relates to communicating the topic of climate change to cattle producers. Three focus groups, comprised of 29 attendees of the workshop, were conducted simultaneously at the end of the conference. Specific themes about trust included the politically charged nature of climate change, climate change data manipulation, negativity of media surrounding climate change, weathercasters getting predictions wrong, agriculture getting a “black eye” with the public, and participants’ relationships with cattle producers. Findings indicate varying levels of distrust, related to sources of information and influence on the topic of climate change, greatly impact how and whether Extension Service and NRCS employees actually talk “climate change” to cattle producers. Based on the study’s findings, it is recommended that for Extension and NRCS employees to talk about controversial issues, like climate change, it is important to create relationships with clients. In addition, communication and education professionals working with cattle producers should avoid politicizing the topic of climate change if they want climate-related programs to be accepted.
Keywords: climate change; cattle; Extension; trust